Post Systolic Motion – A Marker for Ischemia in Left Bundle Branch Block - R, Praveen Babu; S, Arun kumar; V, Sakthivel (Cardiology and Cardiovascular Medicine, 2022)
Background: To diagnose ischemia in patients with left bundle branch block (LBBB) patients non-invasively is always a diagnostic challenge. Many of the non-invasive modalities like stress test, nuclear imaging, cardiac CT and MRI that are routinely used to detect ischemia in recent times have their own limitations when used in patients with LBBB. Tissue Doppler imaging (TDI) has shown promising results in detecting ischemia in LBBB patients in various studies. Methods: The study population was divided into two groups. Group one included 22 patients with LBBB with left anterior descending artery (LAD) stenosis > 50%. Group two includes 29 patients with LBBB with no or < 50% LAD stenosis. Both groups were subjected to TDI. Results: TDI showed low myocardial systolic velocities (Sm), high late diastolic velocities (Am) and high post-systolic motion (PSM) in patients with LAD stenosis. PSM > 6.3 m/s and Sm/ PSM ratio ≤ 0.8 detected LAD stenosis with 77% sensitivity and 96% specificity. Conclusions: TDI may be useful to identify ischemia in patients with LBBB.